Konsep Dasar Sistem Informasi Manajemen (SIM) (Basic Concept of Management Information System (MIS)) - Aissy Rafiatunnisa; Dwi Meli Noviani (Lentera Pendidikan: Jurnal Ilmu Pendidikan dan Keguruan Islam, 2025)
This study discusses the Educational Management Information System (EMIS), which is a combination of three main components: system, information, and management. A system is defined as a group of interacting elements to achieve a common goal, while information is data that has been processed into a more meaningful and useful form for decision-making. Management refers to the process of managing resources to achieve organizational goals effectively and efficiently. In the context of education, EMIS serves to collect, process, and disseminate information needed in the educational management process. Furthermore, EMIS also plays an important role in the planning, control, and evaluation of educational activities. With this system, education managers can make more accurate and data-based decisions, thereby improving the overall quality of education. This study emphasizes the importance of applying information technology in educational management to support the development of a better education system.